Pengembangan e-Modul STEM Berbasis Project Based Learning Pada Materi Unsur Golongan Halogen Untuk Kelas XII SMA - Tania Aulia Putri; Siti Rahmah (Universitas Negeri Malang, 2023)
Abstract: This research is a research on the development of teaching materials in the form of Project Based Learning STEM E-Modules on Halogen Elements Material for Class XII SMA. Development of teaching materials based on STEM and PjBL is needed as a learning solution in the 21st century. In addition, the use of electronic teaching materials is in line with the development of technology 4.0. This study aims to: 1) Determine the validity of the developed PjBL-based STEM E-Module; 2) Knowing student responses to the developed PjBL-based STEM E-Module. The sample chosen in this study was students of class XII MIPA 5 SMA Negeri 1 Kisaran. The development model in this study uses the 4D model. This research consists of 4 steps, namely define, design, develop, and disseminate. The results showed that: (1) the STEM E-Module Based on Project Based Learning was declared